The combined effects of salt feed, photoperiod, and temperature on Atlantic salmon smolt physiology, migratory behaviour, and sexual maturation - Lars Eirik Myklatun; Antony J. Prabhu Philip; Angelico Madaro; Audun Ø. Pedersen; Thomas W.K. Fraser; Trygve Sigholt; Tom J. Hansen; Birgitta Norberg; Sigurd Stefansson; Per Gunnar Fjelldal (Aquaculture, 2027)

A Review on the Effects of the Doubled Maternal Genome in Triploids With a Suggested Pathway to Improving Their Performance in Aquaculture by Purging Deleterious Genes - Tom J. Hansen; Alison C. Harvey; Angelico Madaro; Aurélien Delaval; Kevin A. Glover; Monica F. Solberg; Thomas W. K. Fraser; Per Gunnar Fjelldal (Reviews in Aquaculture, 2025)
Triploid fish are usually sterile, a trait which reduces unwanted sexual maturation in fish farming and eliminates the risk for negative genetic effects of escapees on wild stocks. The triploid state, normally established through a doubling of the maternal genome, consists of two chromosome sets from the mother and one from the father. The increase in genome size is accompanied by an increase in cell volume and reduction in cell number that are associated with physiological effects which have been described in several studies. The doubled maternal genome is also mirrored in the triploid phenotype whereby meristic characters, growth, and physiology, are commonly biased towards that of the dam. However, chromosome doubling techniques are also known to give strong inbreeding effects. In meiotic gynogenes, this is seen in fitness‐related traits such as reduced survival, especially during early life, an increase in deformities, and lower growth. The same effects on fitness, although to a milder degree, are seen in triploids, which supports the hypothesis that they are also affected by inbreeding. Producing triploids by interploidy alleviate the inbreeding problem as the tetraploids can be crossbred to increase their heterozygosity. However, producing tetraploid broodstocks is both challenging and time and resource demanding. An alternative approach is to establish a triploid founder broodstock through one generation of gynogenesis. The gynogenesis will eliminate the lethal alleles, and by selecting the best performing individuals from the best performing families, one will also partially eliminate recessive deleterious alleles, increasing the fitness of the resulting triploid population.